THE ART OF DEVOTION: EXAMINING RELIGIOUS BODY ART PRACTICES IN GHANA'S GA CULTURE - Asante, Kwesi Kofi (Current Journal of Humanities, Arts and Social Sciences (CJHASS), 2024)
Body marking, a profound and ancient tradition across indigenous Africa, continues to serve as a significant marker of identity, cultural affiliation, and spiritual expression. This practice involves deliberate physical alterations to the skin, typically in the form of permanent incisions or tattoos, which carry deep personal, cultural, and religious meanings. Historically, body marking has been employed for various purposes, including identification, beautification, and religious observance. These markings are designed to be enduring, as the incisions made on the skin are intended to leave lasting scars that are difficult or impossible to fully remove. This paper explores the role of body marking in indigenous African societies, with a focus on its significance as a form of identity and its evolving meanings in contemporary contexts. By examining historical and contemporary practices, this study highlights the cultural, social, and spiritual dimensions of body marking and its enduring impact on individual and collective identities.